1991
DOI: 10.1103/physrevb.44.5966
|View full text |Cite
|
Sign up to set email alerts
|

Fe on Au(100): Quantum-well states down to a monolayer

Abstract: Quantum-well states are observed for Fe films embedded in Au(100) using inverse photoemission.They can be analyzed with a simple interferometer model, using bulk states from the I &26&H» band that are modulated by an envelope function with wavelengths in the order of 7-10 atomic layers (10-14 A). These states can be followed down to a monolayer, where two states are seen at 0.6 and 1.9 eV. They are tentatively assigned to the 551 monolayer state and a A~quantum-well state. The resulting ferromagnetic exchange … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(59 citation statements)
references
References 28 publications
1
58
0
Order By: Relevance
“…11 The segregation of Au was further supported by low-energy electron diffraction 12 and photoemission studies. 13 For the case of Fe deposited on Au/ Fe/ GaAs͑001͒, however, XPS measurements as a function of the top Fe film thickness indicated that Au does not segregate to the surface of Fe.…”
Section: Sample Preparationmentioning
confidence: 99%
“…11 The segregation of Au was further supported by low-energy electron diffraction 12 and photoemission studies. 13 For the case of Fe deposited on Au/ Fe/ GaAs͑001͒, however, XPS measurements as a function of the top Fe film thickness indicated that Au does not segregate to the surface of Fe.…”
Section: Sample Preparationmentioning
confidence: 99%
“…In particular, thin magnetic films and multilayers exhibit a rich variety of properties not previously found in bulk magnetism such as enhanced or reduced moments [2], oscillatory exchange coupling through nonmagnetic spacers [3][4][5], giant magnetoresistance [6,7], and the reorientation of the magnetic easy axis upon thickness and temperature variation [8][9][10][11]. Especially the observation of spin-polarized quantum well states (QWS) [12][13][14][15] in Cu/Co (001) has attracted a great deal of attention. It has become clear that quantum well states are indeed responsible for the important oscillatory behavior of the exchange coupling of ferromagnetic thin films via nonmagnetic spacers [16,17].…”
mentioning
confidence: 99%
“…It has become clear that quantum well states are indeed responsible for the important oscillatory behavior of the exchange coupling of ferromagnetic thin films via nonmagnetic spacers [16,17]. Presently mainly photoemission (PE) and inverse photoemission (IPE) [12][13][14][15] have been used to identify QWS effects. Very recently a possible connection between thickness dependent changes in NOLIMOKE and QWS [18] has been proposed.…”
mentioning
confidence: 99%
“…[27], energy E shows oscillation as a function of N. Since the density of states (DOS) for this case varies as E 1 2 , it will also show oscillation as a function of N at Fermi level. The period of oscillations can be predicted by analyzing the peak positions of QW states in the electronic density of states [25,27]. In Fig.…”
Section: Qw Modelmentioning
confidence: 99%
“…Several models [5,10,25,26] have been presented to explain the period of oscillations of the IEC. The RKKY and QW models express the period in terms of the nesting vectors at the Fermi surface.…”
Section: Comparison With Modelsmentioning
confidence: 99%